2014
DOI: 10.1603/me13169
|View full text |Cite
|
Sign up to set email alerts
|

First Record ofIxodes arboricola(Ixodida: Ixodidae) From Turkey With Presence ofCandidatusRickettsia vini (Rickettsiales: Rickettsiaceae): Table 1.

Abstract: Birds are the specific hosts of many tick species and may contribute to the dissemination of ticks and tick-borne pathogens throughout the world. Determination of ticks infesting birds and their pathogens are important for the detection of natural foci of human pathogens. Unfortunately, there is very limited information about the occurrence of ticks on birds and associated pathogens in Turkey. We performed a tick survey on three passerine bird species; Parus major, Sylvia atricapilla, and Turdus merula. Ticks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 20 publications
0
24
0
1
Order By: Relevance
“…of Pages 4 the Czech Republic and Slovakia. Previously, this rickettsia has been confirmed in I. arboricola and I. ricinus ticks from Spain and in I. arboricola ticks from Turkey (Keskin et al, 2014;Palomar et al, 2012a).…”
Section: Discussionmentioning
confidence: 65%
“…of Pages 4 the Czech Republic and Slovakia. Previously, this rickettsia has been confirmed in I. arboricola and I. ricinus ticks from Spain and in I. arboricola ticks from Turkey (Keskin et al, 2014;Palomar et al, 2012a).…”
Section: Discussionmentioning
confidence: 65%
“…Therefore, tick-host associations and natural cycles of many tick-borne pathogens are still far from being clarified in Turkey. In only recent studies, ticks infesting reptiles and birds have been reported from Southeastern and Black Sea regions in Turkey (Keskin et al , 2014. Other than these, there are reports for Hyalomma aegyptium (L.) collected from Testudo graeca L. (Široký et al, 2014); Hyalomma spp.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they are closely associated with several tick-borne pathogens, such as Crimean Congo hemorrhagic virus, borreliae, and rickettsiae Keskin et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Turkey, Candidatus R. vini was detected in I. arboricola ticks collected from birds in the Kizilirmak Delta (77).…”
Section: Typhus (Epidemic Typhus)mentioning
confidence: 99%